Forming the World View of Primary Class Students Based on the Works of Eastern Thinkers (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
In this article, based on the works of Eastern thinkers, the formation of the worldview of primary school students, the study of educational approaches, ideas, views in the minds of the young generation in their creative activities, and the methods and means of education, and the correct use of them in life use, the importance of education in the educational process, the importance of educational education before education, the quality of education if education is properly formed, and how necessary it is for society to educate a perfect person. There are opinions about this from the fair views of Eastern thinkers. At the same time, as a result of the conducted research, it is necessary to study the works of Eastern thinkers, to organize lessons based on them, and to form children's spirituality.